Teaching in Countryside Education in the context of COVID-19 - Juliana Crespo Lopes; Gabriela Fernandes Chaves Lira; Nicolly Papacidero Magrin; Débora da Silva Noal; Marina Thuane Melo da Silva (Universidade Federal do Norte do Tocantins, 2021)
Education in the countryside is a result of historical fights for the rights of property, education, social justice, and labor. The COVID-19 Pandemic highlighted the existing vulnerabilities and precariousness, and alongside the social isolation came the need to cope with mental health issues and psychosocial support for countryside teachers. This paper aims to present an analysis on the implications of COVID-19 Pandemic in mental and psychosocial health of the countryside teachers. Five countryside education professionals were interviewed, one from each Brazilian region. Online semi-structured interviews were analysed by discourse analysis. The findings showed situations leading to psychological distress as well as critical protective processes, which promoted mental health in the pandemic context. Pedagogical practices from distance have turned the situation of countryside education and its educators even more precarious and vulnerable. The pandemic accelerated processes of depersonalisation and devaluation of countryside education.